Association of nailfold capillaroscopic findings with clinical features in patients with systemic sclerosis - Haque, Tajkia; Shahin, Md. Abu; Islam, Md. Ariful; Bandhan, Iftekhar Hussain; Choudhury, Minhaj Rahim; Haq, Syed Atiqul; Zaman, Mohammad Mostafa (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Microvascular damage is one of the most important etiopathogenetic and clinical characteristics of systemic sclerosis (SSc). Nailfold capillaroscopy (NFC) is a simple, non-invasive, and inexpensive imaging technique to assess the skin microcirculation. The aim of this study was to determine the association between NFC findings and clinical features in patients with SSc. Methods: This study was done in the Department of Rheumatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from July 2019 to August 2020. Twenty-nine adult patients with SSc were selected according to ACR/EULAR (American College of Rheumatology/European Alliance of Associations for Rheumatology) criteria 2013. NFC variables (capillary loss, avascular area, giant capillary, microhemorrhage and neoangiogenesis) and their NFC patterns (nonspecific, early, active, and late scleroderma) were analyzed using a dynamic nailfold capillaroscope. Their associations with disease duration, skin thickness score, interstitial lung disease (ILD), pulmonary hypertension (PH) and peripheral vascular involvement (pitting scar, and others) were examined. Results: Among 29 patients, scleroderma patterns were present in 27 (93.1%) patients. Thirteen (44.8%) patients had late scleroderma pattern. Early scleroderma pattern and active scleroderma patterns were observed in 7 (24.1%) patients. Disease duration was significantly associated with avascular area (P=0.04) and NFC pattern (P=0.001). Microhemorrhage was significantly associated (P=0.04) with PH, but NFC pattern was associated with ILD (P=0.03). Conclusion: NFC pattern found to be significantly associated with disease duration and ILD. Among the individual NFC findings, avascular area shows association with disease duration and microhaemorrhage showed association with pulmonary hypertension in SSc patients.